ELABORAÇÃO DA LEI MUNICIPAL DE AGROECOLOGIA DE FERNANDES PINHEIRO, PR: UM TRABALHO INTERDISCIPLINAR - França, Mauricila de Campos (2016)
Agroecology is characterized as a collective social action sectors of civil society, linked to the management of environmental resources. Also, it is recognized as a new way to promote sustainable rural development. The company's initiatives to promote agroecology show positive responses whenever rely on public policy stimuli. These are fundamental to contribute to the development of agroecology directed to family farmers. The objective of the research was to develop the Municipal Act Agroecology in Fernandes Pinheiro, PR, through an interdisciplinary perspective, to contribute to sustainable community development in the region. We evaluated socioeconomic data and conducted needs assessment of 8 families of agroecological farmers Bituva dos Machados community, Fernandes Pinheiro, PR. The team was formed by professionals belonging to the Municipality of Fernandes Pinheiro linked to Federal Programs to Support Family Agriculture, county farmers and representatives of civil society. For the preparation of Law was held the First Municipal Seminar on Agroecology with interdisciplinary approach. The aim was to clarify issues related to agroecology and discuss, through working groups, items related to the needs of family farmers that should be present in the Act. As a result, the researchers used the Law No. 17190, the diagnosis of reported needs for farmers and items suggested by Seminar working groups to draft Municipal Act Agroecology Fernandes Pinheiro, PR. The knowledge and difficulties encountered during the preparation of the Law were published in the 14th Day of Agroecology that occurred in the city of Irati, PR. The results showed that farmers work permanently in agriculture; have adequate housing; its products are marketed with the Municipality; adopt ecological and sustainable techniques for soil conservation; They have little technical guidance and; productivity among low levels in the medium. All farmers are certified and work with agroecology because of higher income. As difficulties, farmers reported the lack of adequate machinery and planting larger crops. The realization of the First Municipal Seminar of Agroecology contributed effectively to improve the deepening of the factors to be listed in the drafting of the Law The difficulties observed in the research were the incomplete filling of questionnaires.; poor condition of community access roads low adherence of researchers in the course of activities and; disinterest of the Legal Sector Fernandes Pinheiro Prefecture to assist in drafting the law. Disclosure of all the work on the 14th Day of Agroecology can be considered as a positive alternative, aiming to collaborate with other professionals interested in the area. It is concluded that farmers resident in Bituva Community dos Machados have different needs to be resolved by the public administration. However, the work of an interdisciplinary team can intervene in an effective way in developing a Municipal Law Agroecology, to contribute to improve the problems of this population at the local, regional and national level.